VIDEO MOTION GRAPHIC “SELF-ESTEEM” SEBAGAI INFORMASI BAGI REMAJA: “Self-Esteem” Motion Graphic Video as Information for Adolecents - Sevinevita Kausalya Atjil; Intan Permata Sari; Nurhidayatulloh (Universitas Trisakti, 2025)
“Self-Esteem” Motion Graphic Video as Information for Adolecents. Adolescents have the idea that they feel useless, have no self-satisfaction, and have low self-esteem. The self-esteem that occurs from acne makes teenagers more likely to judge their self-image negatively. Low self-esteem due to acne can be improved by providing information. Therefore, researchers chose one-way communication media, namely motion graphics. The research method is to use MDLC (Multimedia Development Life Cycle) which includes six stages, namely concept, design, material collection, assembly, testing and distribution. The results of this research show that information media about self-esteem for teenagers using motion graphic techniques is very feasible. From the results of expert and adolescent testing, it is known to designers that self-esteem motion graphics for adolescents are well received and help adolescents increase their self-esteem.